Hot tool steel powder for laminated forming and hot tool steel laminated forming article
By preparing heat-processing hot-process tool steel powder with specific components, the problem of easy cracks during the lamination and process is solved, and a thermal-process tool steel layer stacked products with high crack resistance, good high temperature strength and room temperature toughness are achieved.
Patent Information
- Application Number
- CN202380067115.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-21
- Filing Date
- 2023-09-21
- Publication Date
- 2025-04-25
AI Technical Summary
During the lamination and forming process, hot-working tool steel is prone to cracks, especially in large molds or molds with stress concentrations.
By preparing a specific layered-forming hot-forming tool steel powder, the components include C: 0.10% to 0.25%, Si: 0.01% to 0.5%, Mn: 1.5% or less, Cr: 3.0% to 6.0%, Mo and W: 2.0% to 3.5%, V: 0.3% to 0.7%, Ni: 0% to 0.5%, Cu: 0% to 0.25%, and satisfying the specific element composition index, the crack resistance of the material is improved.
By using the hot-working tool steel laminated shapes prepared with this powder, crack resistance during shape is significantly improved, high temperature strength, room temperature ductility and toughness are ensured, and are suitable for high-demand applications such as die-casting molds.
Smart Images

Figure CN119894622A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to hot working tool steel powder for laminated forming and a hot working tool steel laminated formed product. Background Art
[0002] Hot working tool steels such as hot forging dies and die casting dies require high temperature strength, toughness, and wear resistance because they are in contact with high temperature workpieces. In the past, SKD61 or improved steels of SKD61, a Japanese Industrial Standards (JIS) steel grade, were used for hot working tool steels to meet these requirements.
[0003] In addition, recently, the stacking method has attracted much attention as a method that can easily form metal products (parts) with complex shapes in near net shape. The so-called stacking method is an additive manufacturing technology (additive manufacturing) that is also commonly referred to as three-dimensional (3D) printing. Moreover, as types of stacking methods, there are, for example, a powder spray method that stacks metal powder while irradiating it with a heat source to melt it; or a powder bed method that repeatedly irradiates the metal powder spread on the carrier with a heat source to melt it and solidify it, and then stacks it. Through the stacking method, metal products with complex shapes can be made by greatly omitting the previous mechanical processing steps, so difficult-to-process metal materials can be used. Moreover, the difficult-to-process metal materials are also specially high-strength metal materials, so metal products with complex shapes and long durability can be made.
[0004] Furthermore, a laminated formed product is proposed which uses hot working tool steel for metal materials and is produced by the laminated forming method. For example, in Patent Document 1, a laminated forming hot working tool is proposed, which has the following composition: in terms of mass %, it contains C: 0.3% to 0.5%, Si: 2.0% or less, Mn: 1.5% or less, P: 0.05% or less, S: 0.05% or less, Cr: 3.0% to 6.0%, one or two of Mo and W based on the relationship (Mo+1 / 2W): 0.5% to 3.5%, V: 0.1% to 1.5%, Ni: 0% to 1.0%, Co: 0% to 1.0%, Nb: 0% to 0.3%, and the remainder is Fe and impurities, and in a cross section parallel to the stacking direction, the area is 1 μm 2 The area ratio of the above defects is 0.6% or less.
[0005] Patent Document 2 discloses a steel powder for achieving both high thermal conductivity and high corrosion resistance, having the following composition: in terms of mass %, 0.10≦C<0.25, 0.005≦Si≦0.600, 2.00≦Cr≦6.00, -0.0125×[Cr]+0.125≦Mn≦-0.100×[Cr]+1.800··Formula (1) (where , where [Cr] in formula (1) represents the mass % of Cr content), 0.01≦Mo≦1.80, -0.00447×[Mo]+0.010≦V≦-0.1117×[Mo]+0.901··Formula (2) (wherein [Mo] in formula (2) represents the mass % of Mo content), 0.0002≦N≦0.3000, and the remainder is Fe and unavoidable impurities.
[0006] Prior art literature
[0007] Patent Literature
[0008] Patent Document 1: International Publication No. 2019 / 220917
[0009] Patent Document 2: Japanese Patent Application Publication No. 2016-145407 Summary of the invention
[0010] Problems to be solved by the invention
[0011] As described above, several steels for laminated molding have been proposed, but cracks may occur during molding depending on the type of molding machine, molding conditions, molding size, etc. For example, large laminated molding molds or laminated molding molds with stress concentration portions (concave portions) tend to be prone to cracks.
[0012] Therefore, an object of the present invention is to provide a hot working tool steel powder for laminated molding, which can obtain a hot working tool steel laminated molded product capable of further improving the crack resistance during molding.
[0013] Technical means of solving problems
[0014] The present invention has been made in view of the above-mentioned problems.
[0015] That is, one embodiment of the present invention is a hot working tool steel powder for laminated forming, which contains, in mass %, C: 0.10% to 0.25%, Si: 0.01% to 0.5%, Mn: 1.5% or less, Cr: 3.0% to 6.0%, one or two of Mo and W based on the relationship formula (Mo+1 / 2W): 2.0% to 3.5%, V: 0.3% to 0.7%, Ni: 0% to 0.5%, Cu: 0% to 0.25%, and the remainder: Fe and inevitable impurities, and satisfies the formula (1): C+Si / 30+(Mn+Cr+Cu) / 20+Ni / 60+(Mo+1 / 2W) / 15+V / 10≦0.75 (the symbols of each element in the formula (1) represent the content (mass %) of the element).
[0016] In addition, another embodiment of the present invention is a hot working tool steel laminated formed product, which contains, in mass %, C: 0.10% to 0.25%, Si: 0.01% to 0.5%, Mn: 1.5% or less, Cr: 3.0% to 6.0%, one or two of Mo and W based on the relationship formula (Mo+1 / 2W): 2.0% to 3.5%, V: 0.3% to 0.7%, Ni: 0% to 0.5%, Cu: 0% to 0.25%, and the remainder: Fe and unavoidable impurities, and satisfies the formula (1): C+Si / 30+(Mn+Cr+Cu) / 20+Ni / 60+(Mo+1 / 2W) / 15+V / 10≦0.75.
[0017] Effects of the Invention
[0018] According to the present invention, it is possible to obtain hot working tool steel powder for laminated molding, which is capable of molding a hot working tool steel laminated molded product having excellent crack resistance during molding. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] [ Figure 1 ] is a cross-sectional observation photograph parallel to the lamination direction of the hot work tool steel laminated product of the example of the present invention.
[0020] [ Figure 2 ] is a cross-sectional observation photograph of a hot work tool steel laminated product of a comparative example parallel to the lamination direction.
[0021] [ Figure 3 ] is a cross-sectional observation photograph parallel to the stacking direction of a hot working tool steel laminated product of another comparative example. DETAILED DESCRIPTION
[0022] The present invention has the following composition: C: 0.10% to 0.25%, Si: 0.01% to 0.5%, Mn: 1.5% or less, Cr: 3.0% to 6.0%, one or both of Mo and W based on the relationship of (Mo+1 / 2W): 2.0% to 3.5%, V: 0.3% to 0.7%, Ni: 0% to 0.5%, Cu: 0% to 0.25%, and the remainder: Fe and inevitable impurities. First, the reasons for limiting the composition of the hot working tool steel powder for laminated molding specified by the present invention are described. In addition, unless otherwise specified, "%" means "mass %".
[0023] C: 0.10%~0.25%
[0024] C is a basic element for hot working tools that partially dissolves in the matrix to impart strength and partially forms carbides to improve wear resistance or sintering resistance. In addition, when C and Cr, which are dissolved as interstitial atoms, are added together with substitutional atoms with high affinity for C, it is an element that is expected to contribute to the I (interstitial atom)-S (substitutional atom) effect (acting as a drag resistance of solute atoms and increasing the strength of hot working tools), and is also an element that can improve hardenability. If C is too low, a ferrite phase is mainly formed during solidification, and since the main phase becomes a ferrite phase until room temperature, the quenching required for rapid cooling from the austenite phase cannot be performed. If the main phase from just after solidification to room temperature is a ferrite phase, the thermal contraction that utilizes the expansion of the martensitic phase transformation cannot be alleviated, and it is also easy to crack. However, if C becomes more, the toughness decreases instead of increasing the hardness, which promotes the easy cracking during forming. In the present invention, in order to improve crack resistance and maintain hardness that can withstand mold use, the content is set to 0.10% to 0.25%. It is preferably 0.12% or more, and more preferably 0.15% or more. In addition, it is preferably 0.22% or less, and more preferably 0.19% or less.
[0025] Si: 0.01%~0.5%
[0026] Si can be used as a deoxidizer when adjusting the component composition of molten steel. Since it is difficult to achieve no addition in manufacturing, it is set to 0.01% or more. On the other hand, if it is too much, ferrite will be generated in the tool structure after tempering. Therefore, it is set to 0.5% or less. Preferably it is 0.4% or less. More preferably, it is 0.3% or less.
[0027] Mn: 1.5% or less
[0028] If Mn is too much, the viscosity of the matrix will increase and the machinability of the material will decrease. Therefore, it is set to 1.5% or less. Preferably, it is 1.0 or less. More preferably, it is 0.75% or less, and more preferably, it is 0.7% or less. On the other hand, Mn has the effect of improving hardenability, inhibiting the formation of ferrite in the tool structure, and obtaining a moderate quenching and tempering hardness. In order to obtain these effects, it is preferably contained at least 0.1%. More preferably, it is 0.25% or more. More preferably, it is 0.45% or more, and more preferably, it is 0.55% or more.
[0029] Cr: 3.0%~6.0%
[0030] Cr is a basic element for hot working tools that improves hardenability and forms carbides, which has an effect on strengthening the matrix or improving wear resistance and toughness. However, if it is too much, it will lead to a decrease in hardenability or high temperature strength. Therefore, Cr is set to 3.0% to 6.0%. It is preferably 5.5% or less. It is more preferably 5.0% or less. It is further preferably 4.5% or less, and it is further preferably 4.3% or less. In addition, it is preferably 3.5% or more. It is more preferably 3.6% or more, and it is further preferably 3.7% or more, and it is further preferably 4.0% or more.
[0031] One or both of Mo and W based on the relationship (Mo+1 / 2W): 2.0% to 3.5%
[0032] Mo and W can be contained alone or in combination in order to precipitate or agglomerate fine carbides through tempering to impart strength, improve softening resistance or high temperature strength. Moreover, in the present invention, in order to improve crack resistance and reduce C, it is expected that at least 2.0% or more of Mo and W are contained to supplement strength. As for the content at this time, since the atomic weight of W is about twice that of Mo, it can be specified together with the Mo equivalent defined by the relationship formula (Mo+1 / 2W) (of course, only one or both can be contained). Moreover, in order to obtain the above effect, more than 2.0% is contained based on the value of the relationship formula (Mo+1 / 2W). More preferably, it is more than 2.1%. However, if Mo or W is too much, it may lead to a decrease in machinability or toughness and a decrease in crack resistance. In addition, since the difficulty of melting at a high melting point increases, it is not preferred to contain a large amount of it in terms of manufacturing. Therefore, it is set to be less than 3.5% based on the value of the relationship formula (Mo+1 / 2W). It is more preferably 3.0% or less, and still more preferably 2.5% or less.
[0033] V: 0.3%~0.7%
[0034] V has the effect of forming vanadium carbides to strengthen the matrix or improve wear resistance and temper softening resistance. Moreover, when the stacked shape formed in the stacked forming process is heated to the quenching temperature and "quenched", the vanadium carbide also acts as a "pinning particle" that suppresses the coarsening of austenite grains during quenching heating, which helps to improve toughness. However, since V has a high carbide generation ability, if V is too much, all C will become vanadium carbides, and other carbides may not be generated. Tool steel is established by the presence of multiple carbides, so it is not ideal for the carbide to be only vanadium carbide. Therefore, V is set to 0.3% to 0.7%. Preferably, it is 0.4 or more, and more preferably 0.5% or more. In addition, it is preferably 0.6% or less.
[0035] Ni: 0%~0.5%
[0036] Ni is an element that inhibits the formation of ferrite in the tool structure. In addition, it is an element that is effective for the following: together with C, Cr, Mn, Mo, W, etc., it imparts excellent hardenability to the tool material, and forms a martensite-based structure even when the cooling rate during quenching is slow, thereby preventing a decrease in toughness. Furthermore, since it also improves the intrinsic toughness of the matrix, it can also be contained in the present invention as needed. When contained, it is preferably 0.1% or more. However, too much Ni is an element that increases the viscosity of the matrix and reduces machinability. Therefore, even when Ni is contained, it is set to 0.5% or less. It is preferably 0.3% or less, and more preferably 0.2% or less.
[0037] Remainder: Fe and unavoidable impurities
[0038] The remainder is Fe and inevitable impurities. As inevitable impurities, elements such as P, S, Cu, Al, Ca, Mg, O (oxygen), N (nitrogen), and B (boron) can be listed, and these elements are preferably as low as possible. However, on the other hand, in order to obtain additional effects such as morphological control of inclusions, or other mechanical properties, and improvement of manufacturing efficiency, a small amount may also be contained. In this case, as long as it is within the range of Al≦0.04%, Ca≦0.01%, Mg≦0.01%, O≦0.05%, N≦0.05%, and B≦0.05%, it can be fully allowed, which is the preferred upper limit of the present invention. Regarding Al, it is more preferably 0.025% or less. Moreover, in particular, in terms of suppressing cracks during the stacking molding described later, Cu needs to be limited to less than 0.25%. In addition, P and S can be based on SKD61 as a JIS steel grade, for example, P≦0.030% and S≦0.020%.
[0039] Formula (1): C+Si / 30+(Mn+Cr+Cu) / 20+Ni / 60+(Mo+1 / 2W) / 15+V / 10≦0.75
[0040] In the present invention, in addition to the composition regulations, the left side of the formula (1) is adjusted to be less than 0.75. The left side of the formula (1) is a modified Pcm used as a low-temperature crack sensitivity index for welding, and C, Si, Mn, Cr, Cu, Ni, Mo, W, and V in the formula (1) represent the content (mass %) of each element. Welding is also a problem in the same way as stacking forming. In addition, both are molten solidification structures, so it is found that it is an index that can be used to suppress cracks in stacking forming and is applied to the present invention. Here, the crack index of welding is also known as the hot crack sensitivity index (Hot Cracking Susceptibility Index, HCS) as a high-temperature crack index, but according to previous studies, the forming cracks of this composition system start to break sharply from the surface, which is different from the morphology of high-temperature cracks that are easily generated at the solidification interface, etc. Since the forming cracks of this composition system are visible in the part where tensile stress due to thermal shrinkage is easily generated, they are generated at low temperatures. Therefore, it is presumed that it is similar to the low-temperature cracks of welding, and Pcm, which is a low-temperature crack index, is applied in the present invention. By adjusting each main component so that the left side of formula (1) is 0.75 or less, a powder that can further suppress cracks during forming can be obtained. The upper limit of the preferred Pcm is 0.70.
[0041] The hot-working tool steel powder for laminated molding of the present invention can be produced, for example, by gas atomization or water atomization, disk atomization, plasma atomization, rotating electrode method, etc. Among them, the gas atomization method is a method in which a molten raw material prepared in a manner to have a desired component composition is heated to a temperature above its melting point by high-frequency induction heating, and after melting, an inert gas such as argon or nitrogen is sprayed on the molten metal flowing out through fine holes, thereby finely crushing the molten metal and causing it to solidify rapidly to obtain a powder. The gas atomization method can use scrap metal or metal raw material for melting the raw material, and can be produced at a low cost compared to the plasma atomization method or rotating electrode method that requires the raw material of the desired component composition and shape to be prepared in advance, and is suitable as a method for obtaining the metal powder for laminated molding of the present invention.
[0042] The hot working tool steel powder for laminated molding of the present invention preferably has a 50% particle size (hereinafter referred to as "D50") of 10 μm to 250 μm in the cumulative particle size distribution based on volume. By setting the D50 of the metal powder for laminated molding of the present invention to 250 μm or less, the melting of the powder becomes easy, and the formation of internal defects in the laminated molded product can be suppressed.
[0043] Furthermore, the metal powder for lamination molding of the present invention is less susceptible to the influence of moisture and the like in the atmosphere during the handling of the metal powder or lamination molding by setting its D50 to 10 μm or more, and thus can ensure good fluidity.
[0044] The cumulative particle size distribution of the molding powder of the present invention is represented by a cumulative volume particle size distribution, and D50 thereof can be represented by a measured value by a laser diffraction scattering method specified in JIS Z 8825.
[0045] According to the method, the hot working tool steel powder for stacking forming of the present invention can also be adjusted by screening and grading using a screen or air flow grading, etc. to adjust the D50 of the metal powder. For example, the metal powder for stacking forming used in the powder bed method is melted by a laser beam as a heat source. On the other hand, in order to minimize the range of heat influence, it is necessary to remove coarse metal powder that is difficult to melt. In addition, in order to obtain the optimal fluidity for ensuring the laying property of the metal powder, it is also necessary to remove fine metal powder with high adhesion. Therefore, when the maraging steel powder for stacking forming of the present invention is applied to the powder bed method, it is preferred to adjust the D50 to within the range of 10 μm to 53 μm. The preferred upper limit of D50 is 40 μm, and the preferred lower limit of D50 is 20 μm.
[0046] By laminating the hot working tool steel powder for laminating molding of the present invention using the manufacturing method described below, a hot working tool steel laminating molded product can be obtained, which contains, by mass%, C: 0.10% to 0.25%, Si: 0.01% to 0.5%, Mn: 1.5% or less, Cr: 3.0% to 6.0%, one or two of Mo and W: 2.0% to 3.5% based on the relationship of (Mo+1 / 2W), V: 0.3% to 0.7%, Ni: 0% to 0.5%, Cu: 0% to 0.25%, and the remainder: Fe and inevitable impurities, and satisfies the formula (1): C+Si / 30+(Mn+Cr+Cu) / 20+Ni / 60+(Mo+1 / 2W) / 15+V / 10+≦0.75. The laminating molded product is excellent in that it is not easy to generate molding cracks and has good high temperature strength, room temperature ductility, and toughness. Here, the high temperature strength of the present invention can be evaluated by using a test piece tempered to a hardness of 44 Rockwell hardness (HRC) ± 2 HRC, and the 0.2% proof strength obtained by a tensile test in a high temperature environment of 550°C, and is preferably 900 MPa or more. The more preferred lower limit of the 0.2% proof strength is 930 MPa, and the further preferred lower limit of the 0.2% proof strength is 950 MPa. In addition, the room temperature ductility and toughness of the present invention can be evaluated by using a test piece tempered to a hardness of 44 HRC ± 2 HRC, and the drawing or Charpy impact value obtained by a tensile test in a room temperature (e.g., 22°C) environment. The preferred drawing is 60% or more, and more preferably 63% or more. In addition, the preferred Charpy impact value is 30 J / cm 2 More preferably, 50 J / cm 2 More than 80 J / cm 2 More than 100 J / cm 2 The 0.2% proof stress or elongation can be measured by a tensile test based on JIS Z 2241, and the Charpy impact value can be measured by a 2 mm U-notch Charpy impact test based on JIS Z 2242.
[0047] The stacked molded product is the most preferred application example of a die casting mold, but it is also possible to be applied to molds that require internal cooling mechanisms such as other plastic molds. In addition, there is also the possibility of being applied to the repair of a stacked mold using a powder spray method.
[0048] Next, an example of a production process for obtaining a laminated product of the present invention using the hot working tool steel powder for laminated molding of the present invention will be described in order. In addition, the production process described below is assumed to be a powder bed method unless otherwise specified.
[0049] In the manufacturing method of the present invention, a process of spreading the prepared hot working tool steel powder for stacked molding of the present invention (hereinafter also referred to as "metal powder") into layers, and a process of forming a solidified layer by successively melting and solidifying the spread metal powder using a scanning heat source having a diameter larger than the D50 of the metal powder. Then, by repeating the process of spreading the metal powder into layers and the process of forming the solidified layer, a plurality of layered solidified layers are formed, and the stacked molding of the present invention can be produced. The scanning heat source can be, for example, a laser or an electron beam. Moreover, by making the diameter of the scanning heat source larger than the D50 of the metal powder, the collection of metal powders can be melted evenly, which is preferred in this respect.
[0050] In the manufacturing method of the present invention, the laser output power when the laser is scanned and irradiated to the metal powder can be set to 50 W to 350 W, the scanning speed can be set to 200 mm / second to 2000 mm / second, and the scanning pitch can be set to 0.02 mm to 0.20 mm. Here, if the stacking thickness of each laser scan is too large, it is difficult to transfer heat to the entire metal powder when the laser is irradiated, and the metal powder is not fully melted, which promotes the generation of internal defects. On the other hand, if the stacking thickness of each scan is too small, the number of stackings until the size of the specified stacked formed product becomes more, and the time required for the stacking forming process becomes longer. Therefore, the stacking thickness of each scan is preferably set to 10 μm to 200 μm. The more preferred lower limit of the stacking thickness is 20 μm, and the more preferred upper limit of the stacking thickness is 100 μm. In addition, a preheating process may be performed before the stacking molding process. However, since the powder of the present invention has improved crack resistance compared to conventional hot working tool steel powder, for example, if the molded product has few stress concentration areas and is small, the preheating before stacking molding can be omitted.
[0051] In the manufacturing method of the present invention, in order to impart the mechanical properties required for use as a metal product, it is preferred to perform a tempering treatment at a temperature of 500°C to 700°C on the component that maintains the laminated shape (a state in which heat treatment is not performed after the laminated shape). By performing the tempering, it can be adjusted to a product of a "laminated shape hot working tool" having a specified hardness. Moreover, during this period, the laminated shape can be adjusted to the shape of a hot working tool by various mechanical processing such as cutting or punching. In this case, in order to facilitate mechanical processing, the laminated shape formed in the laminated shape process can be annealed. Annealing can also be expected to have the effect of making the vanadium carbide in the structure of the laminated shape hot working tool after tempering fine. Moreover, finishing machining can also be performed after tempering. In addition, depending on the situation, the laminated shape that has been tempered can also be subjected to the above-mentioned mechanical processing according to the above-mentioned finishing machining, so as to be finished into a product of a laminated shape hot working tool.
[0052] Furthermore, quenching may be performed before the tempering. Furthermore, the stacked structure formed in the stacked structure step may be annealed regardless of whether the annealing is performed or before or after the annealing.
[0053] The tempering temperature varies depending on the target hardness, etc., but is generally about 500°C to 700°C. In addition, when quenching is performed before tempering, the quenching temperature is generally about 900°C to 1100°C. For example, in the case of SKD61, which is a representative steel type of hot work tool steel, the quenching temperature is about 1000°C to 1030°C, and the tempering temperature is about 550°C to 650°C.
[0054] Moreover, the tempering hardness is preferably set to 50 HRC (Rockwell hardness) or less or 520 Vickers hardness (Vickers Hardness, HV) or less. More preferably, it is 48 HRC or less or 500 HV or less. In addition, it is preferably set to 40 HRC or more or 380 HV or more. More preferably, it is 42 HRC or more or 400 HV or more. In addition, in the present invention, the hardness can be measured according to the measurement method described in JIS Z2245 "Rockwell hardness test-test method" or JIS Z 2244-1 "Vickers hardness test-Part 1: Test method", and Rockwell C scale hardness (HRC) or Vickers hardness (HV) can be used.
[0055] Example
[0056] (Example 1)
[0057] After preparing each metal raw material in a manner to have the component composition shown in Table 1, it is loaded into a high-frequency induction melting furnace and melted, and the molten metal is crushed using argon gas to obtain a gas atomized powder. The value (Pcm) of formula (1) of each sample is also shown in Table 1. For the obtained atomized powder, the particle size is adjusted by screening and air flow classification using a sieve to obtain a powder for stacking molding of the present invention example and the comparative example with a D50 of 35 μm. For each of the obtained metal powders for stacking molding, Mlab cusing 200R manufactured by GE Additive was used to produce stacked moldings under the molding conditions shown in Table 2. In addition, preheating of the base plate was not performed during molding.
[0058] [Table 1]
[0059]
[0060] [Table 2]
[0061]
[0062] First, cracks were confirmed in the laminated products with a length of 10 mm × width of 10 mm × height of 11 mm by cross-sectional observation. Cracks were confirmed in the product of sample No. 2 under all molding conditions of molding No. 11 to No. 30. Cracks were confirmed in sample No. 3 under molding conditions No. 11, molding conditions No. 12, molding conditions No. 16, molding conditions No. 17, molding conditions No. 21, and molding conditions No. 28. As an example, in Figure 1 , Figure 2 , Figure 3 Observation images of the cross sections parallel to the stacking direction (i.e., the cross sections including the stacking interface) of the molded products of sample No. 1, sample No. 2, and sample No. 3 formed under condition No. 28 are shown in FIG. 28. In No. 2 and No. 3, cracks from the surface can be confirmed at the positions indicated by the arrows, but in No. 1 of the present invention example, in which the alloy composition is within the range of the present invention and Pcm is 0.65 or less, no cracks are observed. From the above, it is confirmed that the stacked molded product of the present invention can improve the crack resistance.
[0063] (Example 2)
[0064] Then, various mechanical properties of the laminated formed product of the present invention were evaluated. A gas atomized powder having the alloy composition of sample No. 1 obtained by the same method as in Example 1 was prepared. Then, using M290 manufactured by EOS, a laminated formed product (sample No. 4) of the present invention was produced under the conditions of laser output power: 300 W, scanning speed 800 mm / s, and laminate thickness 0.4 mm. In addition, a steel block having the same composition as sample No. 1 was melted and hot forged to produce a sample of the comparative example (sample No. 5). Table 3 shows the composition of sample No. 4 and sample No. 5. Sample No. 4 was tempered at 550°C and tempered to a hardness of 44 HRC ± 2 HRC. After sample No. 5 was annealed, it was quenched at 900°C, tempered at 570°C to 575°C, and tempered to a hardness of 44 HRC ± 2 HRC, the same as sample No. 4. The hardness was measured using a Rockwell hardness tester in accordance with JIS Z 2245. Then, a tensile test piece and a Charpy impact test piece were collected from the obtained sample No. 4 in the horizontal direction relative to the stacking direction (a cut was processed on the side in the forming direction), and a tensile test piece and a Charpy impact test piece were collected from the sample No. 5 in the forging long side direction (a cut was processed in such a way that the cracks developed on the surface perpendicular to the long side of the forged tensile material and in the direction of the main working force). Then, the obtained tensile test pieces were subjected to a room temperature (22°C) tensile test and a high temperature (550°C) tensile test in accordance with JIS Z 2241, and a 2 mm U-shaped notch Charpy impact test in accordance with JIS Z 2242.
[0065] The results of the obtained mechanical properties are shown in Table 4. According to the results in Table 4, it can be confirmed that the present invention example is a test piece with a hardness of 44 HRC±2 HRC after tempering, and the 0.2% yield strength in a high temperature environment is 960 MPa or more, the room temperature drawing is 65% or more, and the Charpy impact value is 100 J / cm 2 As described above, the high temperature strength, room temperature ductility, and room temperature toughness are all good compared with the comparative example. As one of the reasons for the significant improvement in toughness in the examples of the present invention, it can be considered that the grain size is finer than the molten material of the comparative example. From the above, it is confirmed that the laminated formed product of the present invention can improve the mechanical properties compared with the molten forging material of the same composition.
[0066] [Table 3]
[0067]
[0068] [Table 4]
[0069]
Claims
1. A hot working tool steel powder for laminated molding, comprising, in mass%, C: 0.10% to 0.25%, Si: 0.01% to 0.5%, Mn: 1.5% or less, Cr: 3.0% to 6.0%, one or both of Mo and W based on the relationship (Mo+1 / 2W): 2.0% to 3.5%, V: 0.3% to 0.7%, Ni: 0% to 0.5%, Cu: 0% to 0.25%, and the remainder: Fe and inevitable impurities, and further satisfying the following formula (1), Formula (1): C+Si / 30+(Mn+Cr+Cu) / 20+Ni / 60+(Mo+1 / 2W) / 15+V / 10≦0.75 Here, each element symbol in formula (1) represents the content (mass %) of the element.
2. A hot working tool steel laminated molded product, comprising, in mass%, C: 0.10% to 0.25%, Si: 0.01% to 0.5%, Mn: 1.5% or less, Cr: 3.0% to 6.0%, one or both of Mo and W based on the relationship (Mo+1 / 2W): 2.0% to 3.5%, V: 0.3% to 0.7%, Ni: 0% to 0.5%, Cu: 0% to 0.25%, and the remainder: Fe and inevitable impurities, and further satisfying the following formula (1), Formula (1): C+Si / 30+(Mn+Cr+Cu) / 20+Ni / 60+(Mo+1 / 2W) / 15+V / 10≦0.75 Here, each element symbol in formula (1) represents the content (mass %) of the element.
Citation Information
Patent Citations
Powder of steel and mold using the same
JP2016145407A
Additively manufactured hot work tool, method for manufacturing same, and metal powder for additively manufactured hot work tool
WO2019220917A1